OFC/NFOEC 2007 - 2007 Conference on Optical Fiber Communication and the National Fiber Optic Engineers Conference 2007
DOI: 10.1109/ofc.2007.4348548
|View full text |Cite
|
Sign up to set email alerts
|

140 Carrier, 20GHz SCM Signal Transmission across 200km SMF by Two-step Sideband Suppression Scheme in Optical SSB Modulation

Abstract: We propose a two-step sideband suppression scheme to realize enhanced optical SSB generation. 140 carrier, super wideband (8GHz to 20GHz) SCM transmission across 200km of SMF is demonstrated. The scheme achieves high sideband suppression ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…An SSR of 13 dB was achieved directly with a DD-MZM in [3]. Larger SSR values, up to 28 dB, have been reported but using additional and costly optical filters [12,13]. Fig.1 shows a spectrally efficient WDM/SSB transmitter without additional optical filters; where performance is limited due to the crosstalk associated with the imperfect suppression ratio.…”
Section: Introductionmentioning
confidence: 99%
“…An SSR of 13 dB was achieved directly with a DD-MZM in [3]. Larger SSR values, up to 28 dB, have been reported but using additional and costly optical filters [12,13]. Fig.1 shows a spectrally efficient WDM/SSB transmitter without additional optical filters; where performance is limited due to the crosstalk associated with the imperfect suppression ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we generate an OSSB signal by processing an ODSB modulated signal. However, the same processing could be applied to enhance the unwanted sideband suppression ratio of an OSSB signal generated my means of any other method [6,7,[15][16][17][18][19][20][21]. This would increment the complexity of the system, but would reduce the amount of SBS interaction required to achieve a significant sideband suppression ratio.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been found that very high levels of suppression of the unwanted sideband are required in order to achieve sufficient optical phase-shift and amplitude measurement accuracy [4]. In the last years, a number of techniques have been developed for the generation of OSSB signals [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, SSB was originally developed as a method to overcome dispersive fading [32,38]. With that technique, SCM/SSB signals have been transmitted over hundreds of km with no penalty due to chromatic dispersion [39]. Secondly, several independent studies have concluded that the optimum subcarrier spacing for long transmission distance over SSMF is within the range of 2-10 Gbaud [40][41][42][43].…”
Section: Optical Linkmentioning
confidence: 99%